Comparison of Anode Types on Electrical Power and Organic Removal using Microbial Fuel Cells Integrated with Anaerobic Baffled Reactor - Syadzadhiya Qothrunada Zakiyayasin Nisa'; Restu H. A. Murti; Nurvita Cundaningsih; M. Ardiansyah Dwi Tama; Nur Laili A. Mukharomah (Universitas Muhammadiyah Purwokerto, 2025)
The tofu production process produces liquid waste that has a high organic content and has the potential to pollute water bodies if not treated. The combination of Microbial Fuel Cells (MFCs) and Anaerobic Baffled Reactors (ABR) presents an effective solution to treat this liquid waste while generating electricity. The purpose of this study was to analyze the effect of the type of anode in the MFCs-ABR system on electrical power (mW) and COD reduction in tofu liquid waste. The methodology used includes processing tofu liquid waste with variations in the types of zinc and stainless steel anodes. The parameters observed were electrical power and COD reduction efficiency at retention times of 0, 24, 48, 72, and 96 hours. The results showed that the zinc anode produced electrical power reaching 0.38 mW and showed a COD reduction efficiency of 55.85% at 96 hours. The stainless steel anode produced electrical power of 0.18 mW and a COD reduction efficiency of 52.80% at 96 hours. This study shows that the type of anode affects the electrical power generated in the MFCs system.